(untitled) (Kinesiology, 2019)
The aim of the present study was to identify and describe different players’ performance profiles in National Basketball Association regular season and playoff games using new combined tracking and notational-based variables. The sample was composed by 535 balanced games (score differences below or equal to eight points) from the regular season (n=502) and the playoffs (n=33), for a total of 472 players were analysed. The variables included were: team points minus opponent points (on and off court), NET score (player’s on values minus his off values), maximum negative and positive point difference, minutes on court, team’s winning percentage, game pace, defensive and offensive ratings, effective field-goal percentage, free-throws/ field-goals ratio, offensive rebound percentage, turnover percentage, game quarter and player position. The two step cluster analysis was performed to identify the players profiles during regular season and playoff games. The results identified five performance profiles during regular season games and four performance profiles during playoff games. The profiles identified were mainly characterized by the game quarter and the negative NET indicator (players’ performance on court minus their performance off court) in regular season games and the positive NET indicator during playoff games and second and third game-quarters. Coaching staffs can fine-tune these profiles to develop more team-specific models and, conversely, use the results to monitor and rebuild team constitution under the constrained dynamics of the game and competition stages.